Parabiotic immunomodulatory activity of yeast cell wall polysaccharides from Saccharomyces cerevisiae and S. boulardii - Kwang-Rim Baek; Hyun-Ji Lee; Kang-Hyeon Jeong; Bo-Ram Park; Soo-Jung Kim; Seung-Oh Seo (Journal of Functional Foods)
Yeast, particularly Saccharomyces cerevisiae, is widely regarded as a nutritional supplement in the food and feed industries. Notably, Saccharomyces boulardii is promoted as a probiotic strain for its efficacy in gastrointestinal disorders. Despite genetic similarities to S. cerevisiae, S. boulardii is distinguished from S. cerevisiae by unique features like cell wall composition, which is crucial for immune activation. This study evaluated the cell wall polysaccharide contents of S. boulardii and S. cerevisiae and their immunomodulatory activity on Raw 264.7 cell. Results showed an increased secretion of pro-inflammatory factors (TNF-α, IL-6, and NO) and the anti-inflammatory factor IL-10. Remarkably S. boulardii cell extracts had a more pronounced effect than S. cerevisiae cell extracts. The immunomodulatory activity is linked to the MAPK(ERK)/NF-κB pathway, activated by β-glucan and mannan via Dectin-1 and Dectin-2 receptors. This difference in immune response are attributed to variations in content of mannan and β-glucan in their cell walls.